PENGARUH KONSEP DIRI DAN HARGA DIRI TERHADAP KEPERCAYAAN DIRI SISWA DI SMP NEGERI 1 MALALAK - Yulia Saputri; Syawaluddin; Afrinaldi; Fadhilla Yusri (IKIP Siliwangi, 2026)
Students’ self-confidence is an important psychological aspect that supports their academic and social development. Internal factors such as self-concept and self-esteem play a significant role in shaping self-confidence and therefore need to be examined empirically. This study aimed to determine the effect of self-concept on students’ self-confidence, the effect of self-esteem on students’ self-confidence, and the simultaneous effect of self-concept and self-esteem on students’ self-confidence. This research employed a quantitative approach with an associative research design. The population consisted of all seventh- and eighth-grade students at SMP Negeri 1 Malalak, totaling 72 students, and total sampling was applied so that all population members were included as research samples. The research instruments were self-concept, self-esteem, and self-confidence scales developed by the researcher. Data were analyzed using simple linear regression and multiple linear regression. The results indicated that self-concept had a positive and significant effect on students’ self-confidence with a contribution of 35.8%. Self-esteem also showed a positive and significant effect on self-confidence with a contribution of 60.9%. Simultaneously, self-concept and self-esteem contributed 61.0% to students’ self-confidence. These findings highlight the importance of fostering self-concept and self-esteem to enhance students’ self-confidence.